AN ELLIPTIC ELASTIC-PLASTIC ASPERITY MICRO-CONTACT MODEL - Jamari, Jamari (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2006)
A theoretical model for the elastic-plastic contact of ellipsoid bodies is presented in this paper. Contactparameters, such as the mean contact pressure, the contact area and the contact load as a function of the contactinterference are formulated and modeled in the three different contact regimes: elastic, elastic-plastic and fully plastic.The model introduces a new simple method to analyze the complexity of the elliptical integral by an accurateapproximation so that the calculation can be executed very fast.